1994
DOI: 10.1177/106342669400200402
|View full text |Cite
|
Sign up to set email alerts
|

Multisystemic Family Preservation Therapy

Abstract: The increase in the number of serious offenses by adolescents, particularly among minority populations, has drawn attention to these difficult-to-treat youths. This article provides preliminary findings from the Diffusion of Multisystemic Family Preservation (MFP) Services Project, which conducted work with rural African-American and White families who have a chronic or violent adolescent offender at imminent risk for incarceration. Analyses assessed the impact of multisystemic therapy on family functioning (p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 71 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…The mean age of the sample was 15 or 16 years in most cases. Six of the 10 studies had an entirely male sample 56,59,61,62,65,67 and the sample was predominantly male in one other study; 66 only one study had an entirely female sample. 63 In the studies in which ethnicity was reported, the sample was predominantly Caucasian; 56,59,61,62,64,65 in one study the majority of the sample was African American.…”
Section: Setting and Samplementioning
confidence: 99%
See 4 more Smart Citations
“…The mean age of the sample was 15 or 16 years in most cases. Six of the 10 studies had an entirely male sample 56,59,61,62,65,67 and the sample was predominantly male in one other study; 66 only one study had an entirely female sample. 63 In the studies in which ethnicity was reported, the sample was predominantly Caucasian; 56,59,61,62,64,65 in one study the majority of the sample was African American.…”
Section: Setting and Samplementioning
confidence: 99%
“…63 In the studies in which ethnicity was reported, the sample was predominantly Caucasian; 56,59,61,62,64,65 in one study the majority of the sample was African American. 66 The total sample size was small for all of the studies. Only four studies had a total sample size > 50 61,62,64,65 and no studies had a total sample size > 100.…”
Section: Setting and Samplementioning
confidence: 99%
See 3 more Smart Citations